ANALISIS YURIDIS PENGELOLAAN BATAS WILAYAH LAUT DAN PESISIR BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Syahuri, Taufiqurrahman; Sitompul, Euodia Octavia (Esensi Hukum, 2020)
Abstract Indonesia is an archipelagic country with an area of the ocean covering almost two-thirds of the total area of the archipelago which has potential with coastal, oceanic, mineral, oil and natural gas resources, however the boundaries and management of marine and coastal areas are not yet optimal and evenly distributed, especially by the Government. Area. Law Number 23 of 2014 concerning Regional Government has stipulated that the maximum boundary for the provincial sea area is 12 nautical miles, while the limit for regency / municipal marine production is a maximum of 4 miles, if the boundary of the sea area between provinces does not reach the maximum limit, the limit will be divided by the distance equal to the principle of the median line. The division of authority in the management of maritime and coastal boundaries is felt by the regional and central governments. This research is aimed at analyzing the implications of the Regional Government Law on several laws and regulations on marine and fisheries and to find out the ideal division of authority in the management of maritime and coastal boundaries. This study uses a normative juridical methodology approach. This research aims to provide a more detailed explanation regarding policies that regulate aspects of the management of maritime and coastal boundaries as well as the implementation of central, regional and other vertical authorities for the welfare of people in the Sea and Coastal areas. The results of the study can be concluded that the implementation of regional government authority in managing the boundaries of coastal sea areas is the division of concurrent governmental affairs of choice and division of affairs in the marine sector between the Central Government, Provincial Regions and Regency / Cities, especially in the marine and fisheries sector. Keywords: authority, local government, coast. Abstrak Indonesia merupakan negara kepulauan dengan luas wilayah lautan meliputi hampir dua pertiga bagian dari seluruh luas wilayah Nusantara yang memiliki potensial dengan sumber daya pesisir, lautan, mineral, minyak dan gas bumi, namun batas dan pengelolaan wilayah laut dan pesisir belum optimal dan merata khususnya oleh Pemerintah Daerah. Undang-Undang Nomor 23 tahun 2014 tentang Pemerintahan Daerah telah menetapkan bahwa batas maksimal wilayah laut provinsi sejauh 12 mil laut, sedangkan batas bagi hasil kelautan kabupaten/kota maksimal sejauh 4 mil, apabila batas wilayah laut antar provinsi tidak mencapai batas maksimal, maka batas akan dibagi sama jarak dengan prinsip garis tengah (median line). Pembagian kewenangan dalam pengelolaan batas wilayah laut dan pesisir dirasakan oleh pemerintah daerah dan pemerintah pusat. Penelitian ini diarahkan untuk menganalisis implikasi Undang-Undang Pemerintahan Daerah terhadap beberapa peraturan perundang-undangan tentang kelautan dan perikanan serta mengetahui pembagian kewenangan ideal dalam pengelolaan batas wilayah laut dan pesisir. Penelitian ini menggunakan pendekatan metodologi yuridis normatif. Dalam penelitian ini bertujuan untuk memberikan penjelasan lebih terperinci mengenai kebijakan yang mengatur aspek pengelolaan batas wilayah laut dan pesisir serta pelaksanaan kewenangan pusat, daerah dan lembaga vertikal lainnya untuk mensejahterakan masyarakat di wilayah Laut dan Pesisir. Hasil penelitian dapat disimpulkan bahwa pelaksanaan kewenangan pemerintah daerah dalam pengelolaan batas wilayah laut pesisir merupakan pembagian urusan pemerintahan konkuren pilihan dan pembagian urusan bidang Kelautan antara Pemerintah Pusat, Daerah Provinsi dan Daerah Kabupaten/Kota terkhusus pada sektor kelautan dan perikanan.